Health and activity monitoring system (HAMS) - Shah, Amit Rajendra (ProQuest Dissertations & Theses, 2010)
Aging population combined with today's lifestyle and tremendous growth in electronics and communication technology have created numerous applications where continuous monitoring of subject's bio-vital data can play an important role to achieve better quality of life. Technology driven solution to efficiently address disease management and many other related issues is the use of remote monitoring system. In this thesis we propose a connected health platform called Health and Activity Monitoring System (HAMS). HAMS architecture and design is efficient to provide anytime, anywhere connectivity solution where the users health data is recorded, transmitted, extracted and deposited on a central repository. The current setup is a system consisting of extremely low power Zigbee compliant wireless sensor nodes (Monitoring Devices + MSP430 + CC2420), a low power mobile hub (Beagle-Board) featuring powerful OMAP-3530 processor from Texas Instruments and a health server, thus providing end-to-end connectivity to the users. This capability assists in monitoring progression of chronic diseases and also provides decision assistance to the caregiver. Sensor-nodes capability to record and store bio-vital data when not connected to the mobile hub along with the implemented time stamping algorithm gives complete mobility to its users. Proposed system also allows users to view his/her graphical trends and thus makes them aware about their personal health. Test were conducted to validate the time stamping algorithm and overall systems usability and modularity. Keywords: Remote Monitoring System, connected health, low power, Zigbee, sensor nodes, mobile hub, time stamping, BeagleBoard, MSP430, OMAP-3530.